RESEARCH OF CYTOPROTECTIVE ACTION OF ANTIOXIDANT DRUGS BY NANOPARTICLES OF CdS AND CdCl2 SALT INTOXICATION - Kozitskaya, T.V.; Savosko, S.I.; Pazyuk, L.M. (World of Medicine and Biology, 2013)
The effects of toxic impact of CdS nanoparticles and CdCl2 salt on cell culture of rat spinal ganglia have been studied. The cytoprotective effect of antioxidant drugs lipin and quercetin on cultured cells has been estimated. It was found out that CdS nanoparticles have considerable toxic impact on pseudounipolar neurons and fibroblasts and EC50 reaches 15 mkmol/l (1,6 mg/ml) for both compounds. The lipin and quercetin application decreases extent of damage and death of cultured cells only if the dose of intoxicants in within 1-10 mkmol/l. The effectiveness of the experimental фармакорекціїi increases with increasing doses of drugs to 30 mg/ml.